Murine IL-4Δ2 splice variant down-regulates IL-4 activities independently of IL-4Rα binding and STAT-6 phosphorylation. (November 2017) - Diogo, Gil R.; Sparrow, Adam; Paul, Matthew J.; Copland, Alastair; Hart, Peter J.; Stelter, Szymon; van Dolleweerd, Craig; Drake, Pascal M.W.; Macallan, Derek C.; Reljic, Rajko
Highlights: Murine version of IL-4Δ2 appears to be fully functional. IL-4Δ2 does not compete with IL-4 for IL-4Rα binding. IL-4Δ2 does not interfere with STAT-6 signalling. Alternative, yet unknown mechanism of IL-4Δ2 modulating IL-4 activity must exist. Abstract: IL-4 is a pleiotropic cytokine that is highly Th2 polarizing. The ratio of IL-4 and its splice variant IL-4Δ2 observed in human health and disease suggests a role for both isoforms. In the present study, the biological function of murine IL-4Δ2 and the potential mechanism of action were studied. We report for the first time the generation of a functional, recombinant murine IL-4Δ2 form which is suggestive of its possible biological role in this species. Recombinant murine IL-4Δ2 inhibited IL-4 mediated cellular processes in macrophages and lymphocytes. Specifically, (i) it reversed IL-4 mediated inhibition of IFN-γ induced nitric oxide release by macrophages, (ii) inhibited IL-4 mediated induction of T cell proliferation, and (iii) prevented IL-4 stimulation of IgE synthesis by B cells. However, IL-4Δ2 did not compete with IL-4 for IL-4Rα binding and did not interfere with the downstream STAT-6 phosphorylation in T cells, suggesting an alternative mechanism for its antagonism of specific IL4-driven effects. These findings suggest that the mouse is a suitable experimental model for studies of the biology of IL-4 and its alternative splice variant.